Comparison of pharmacokinetics and drug release in tissues after transarterial chemoembolization with doxorubicin using diverse lipiodol emulsions and CalliSpheres Beads in rabbit livers - Shuisheng Zhang; Can Huang; Zhengzheng Li; Yongjie Yang; Tingting Bao; Haibo Chen; Yinghua Zou; Li Song (Taylor & Francis Group, 2017)
CalliSpheres® Beads (CB) is the first drug-eluting bead (DEB) product in China. Our aim was to compare the effect on the pharmacokinetics of doxorubicin (DOX) and its local concentration between lipiodol emulsions and CB in the process of TACE in rabbit livers. Twenty-five rabbits were distributed into two groups; Group 1 received lipiodol emulsions with DOX, and Group 2 received CB loaded with DOX (CBDOX). DOX was measured in the peripheral blood at different times after treatment. Livers were sampled at 1 week and 1 month for Group 2 after embolization. DOX concentration and distribution were measured in the liver. The administration of DOX by TACE with CBDOX resulted in peripheral blood DOX concentrations of 39.85 ± 13.86 ng/mL at 5 min, with a gradual decrease to 6.89 ± 1.62 ng/mL at 24 h, after treatment. Plasma concentration of DOX after chemoembolization with lipiodol was 225.91 ± 64.88 ng/mL at 5 min and decreased with time by 24 h to 5.06 ± 0.48 ng/mL. In CBDOX group, the drug impregnated an area as far as 200 μm from the bead edge. The tissue concentration of doxorubicin (tissCDOX) ranged from 40.27 μg/mL to 245.70 μg/mL at 1 week and from 5.64 μg/mL to 28.09 μg/mL at 1 month. Plasma concentrations of DOX resulting from CBDOX embolization were significantly lower than that for cTACE. CB could deliver relatively high concentrations of DOX to an area as far as 200 μm from the bead edge for at least 1 month.